2020
DOI: 10.1002/ps.6192
|View full text |Cite
|
Sign up to set email alerts
|

Multiple origins of a single point mutation in the cotton bollworm tetraspanin gene confers dominant resistance to Bt cotton

Abstract: BACKGROUND Transgenic crops producing insecticidal proteins derived from Bacillus thuringiensis (Bt) are used globally to kill key insect pests and provide numerous benefits, including improved pest management, increased profits, reduced insecticide use, and increased biological control. Unfortunately, such benefits are rapidly being lost by the evolution of Bt resistance by pests. RESULTS The main strategy to delay resistance relies on the use of non‐Bt refuge plants to produce sufficient susceptible insects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…We produced SCD-KI by using CRISPR/Cas9 to knock into SCD a single-base pair substitution (T92C) in a gene (HaTSPAN1) encoding a tetraspanin protein (Jin et al, 2018). The T92C mutation causes non-recessive resistance to Cry1Ac in SCD-KI and occurs naturally in field populations of this pest in China (Jin et al, 2018;Guan et al, 2021). We created C2/C3-KO by using CRISPR/Cas9 to knock out two genes (HaABCC2 and HaABCC3) in SCD encoding the ABC transporter proteins ABCC2 and ABCC3 .…”
Section: Introductionmentioning
confidence: 99%
“…We produced SCD-KI by using CRISPR/Cas9 to knock into SCD a single-base pair substitution (T92C) in a gene (HaTSPAN1) encoding a tetraspanin protein (Jin et al, 2018). The T92C mutation causes non-recessive resistance to Cry1Ac in SCD-KI and occurs naturally in field populations of this pest in China (Jin et al, 2018;Guan et al, 2021). We created C2/C3-KO by using CRISPR/Cas9 to knock out two genes (HaABCC2 and HaABCC3) in SCD encoding the ABC transporter proteins ABCC2 and ABCC3 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, based on its high reliability and low costs, amplicon sequencing has been applied in a series of entomological research, 32–40,46–53 particularly in the detection of the mutation frequency of genes associated with pesticide resistance 30,31 . We detected the frequencies of the L925I and T929V mutations using amplicon sequencing in this study, and found that there was no significant difference in the frequencies of the two mutations in the SX population obtained by Sanger sequencing and amplicon sequencing.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, the frequencies of the T92C mutation in tetraspanin HaTSPAN1 linked with Cry1Ac‐resistance in a geographic population of Helicoverpa armigera in 4 years were detected by the two methods and no significant difference was discovered between the two sequencing data sets 30 . Subsequently, to study the multiple origins of T92C mutation in H. armigera , frequencies of the mutation in 28 field‐collected populations from China were detected by amplicon sequencing and Sanger sequencing, and pair‐wise comparisons between the two data sets showed no significant difference 31 . These findings and our study revealed that amplicon sequencing could be a reliable approach to detect the resistant allele frequencies in insects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations